Ionic density control of conjugated polyelectrolytes via postpolymerization modification to enhance hole-blocking property for highly efficient PLEDs with fast response times - Yan,H; Cong,S; Daboczi,M; Limbu,S; Hamilton,I; Kwon,S; Rapley,CL; Tahir,SM; Kerherve,G; Payne,D; Heeney,M; Kim,J-S (Advanced Optical Materials, 2023)
For an ideal electron interlayer, both electron injection and hole-blocking properties are important to achieve better polymer light-emitting devices (PLEDs) performance. Conjugated polyelectrolytes (CPEs) are applied widely in PLEDs to enhance charge injection. Understanding the role of backbone structures and energetic matching between the CPEs and emitters can benefit charge injection and balance. Herein, a postpolymerization approach to introduce varying amounts of alkyl sulfonate groups onto the backbone of a copolymer of 5-fluoro-2,1,3-benzothiadiazole and 9,9′-dioctylfluorene is utilized. This study finds that device performance is dependent on the percentage of sulfonate groups incorporated, with the optimal copolymer (CPE-50%) maintaining efficient ohmic electron injection and gaining enhanced hole-blocking properties, thereby achieving the most balanced hole/electron current. Therefore, the PLED with CPE-50% interlayer exhibits the highest efficiency (20.3 cd A−1, 20.2 lm W−1) and the fastest response time (4.3 µs), which is the highest efficiency among conventional thin (70 nm) F8BT PLEDs with CPEs. These results highlight the importance of balanced charge carrier density in CPEs and highlight that postpolymerization modification is a useful method for fine-tuning ionic content.